Validity of competency-based architecture textbooks in the concentration of building modeling and information design at SMK Negeri 3 Tanjungpinang - Husain, Farid Muhammad; Nevrita; Kurmalasari, Tety; Malik, Abdul; Abdulhajar, Encik (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Ideally, textbooks used in the learning process at vocational schools should serve as a bridge between theory and practice in the field. However, in reality, the textbooks available at SMK Negeri 3 Tanjungpinang still need improvement. This study aims to determine the validity of the competency-based architecture textbooks that have been developed to support learning in the DPIB Specialization at SMK Negeri 3 Tanjungpinang. This research is R&D research using the ADDIE development model, but this research only confirms the Development stage (validation of the development product). The validation process was carried out by media experts and subject matter experts using a Likert scale-based questionnaire covering aspects of appearance, language, content, and presentation. The data were analyzed descriptively and quantitatively by calculating the total score and determining the level of feasibility. The validation results showed that the textbook obtained a very high level of validity, with a percentage of 98.5% in the learning media aspect and 97% in the learning material aspect. Thus, the average validation results showed that the developed textbook was in the highly valid category, which means that it met the feasibility criteria in terms of content and learning media, making it suitable for use as a learning resource in learning activities at vocational schools.